Pengakuan Kedudukan Hukum Masyarakat Hukum Adat Matteko dalam Pengujian Undang-Undang di Mahkamah Konstitusi - Faiz Rahman (The Constitutional Court of the Republic of Indonesia, 2021)
The constitution states that as long as the customary law community unit and its traditional rights are still alive and in accordance with the development of society and the principles of the unitary state of the Republic of Indonesia, the state recognizes and respects it. However, many problems faced by indigenous peoples have made them aware of their rights, so they have tried several times to make their constitutional rights recognized by positive law. One of them is the Matteko customary law community who lives in Erelembang village, Tompobulu sub-district, Gowa district, South Sulawesi. In order to obtain customary land (forest/land) rights, indigenous peoples must receive recognition and receive recognition in the form of legal products. The purpose of this study was to determine the recognition of the Matteko customary law community in the examination of the Constitutional Court Law and to determine the legal position of the Matteko customary law community in the examination of the Constitutional Court Act. The research method used is empirical normative legal research with primary and secondary data types, where the data sources come from field data and literature. The results of this study are known so far, the Matteko customary law community does not have the legal standing to submit an assessment at the Constitutional Court because it cannot prove recognition as an indigenous community either in the form of a Regional Regulation or a Regional Head Decree. In fact, the legal position of customary law community units in judicial review at the Constitutional Court is clearly stated in the legislation, so that many customary law community units that have not received legal recognition from the state do not have the legal standing to apply for judicial review. Law in the Constitutional Court